2020
DOI: 10.17843/rpmesp.2020.372.5478
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizaje en tiempos de aislamiento social: cursos masivos abiertos en línea sobre la COVID-19

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
6
0
5
Order By: Relevance
“…It was observed that almost one-third of the professionals did not receive any instructions through training or a course on biosafety for COVID-19, which can result in contamination. An alternative to fill this gap may be virtual courses, being a possible educational tool in periods of social isolation [15].…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…It was observed that almost one-third of the professionals did not receive any instructions through training or a course on biosafety for COVID-19, which can result in contamination. An alternative to fill this gap may be virtual courses, being a possible educational tool in periods of social isolation [15].…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…18,29 Regarding the origin of the MOOCs, the largest number were from developed countries, 30 from institutions in Europe and North America, similar results were described in other studies, 11,18,31 being, by default smaller quantity offered by Latin American countries. 32 This predominant origin could be because more than half of the MOOCs were offered and developed in English 11, 18,33 and only 22% in Spanish. Proof of this is that of the 23, 13, and four MOOCs on psychology and mental health, health care, community health and social rights, respectively, only one MOOC for each topic was in Spanish.…”
Section: Discussionmentioning
confidence: 99%
“…Se apoyaron en aulas virtuales, el uso del internet, de redes sociales y el aporte de los docentes, que deben estar familiarizados, preparados para implementar la enseñanza-aprendizaje mediante la virtualidad. (Quijano-Escate, R. et al, 2020).…”
Section: Educación Universitaria ¿Quo Vadis?unclassified